LITHOLOGICAL, MINERALOGICAL AND PETROGRAPHICAL FEATURES OF EOCENIC SANDSTONES OF NORTH-EAST PART OF THE DNEPR-DONETSK DEPRESSION - Derevska, К.; Іsaev, S.; Rudenko, К.; Nurmamedov, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The authors carried out research in the framework of scientific support of the objects of the Geological Reserve "Kaminsky Sandstone"(the part of the Regional landscape park "Seimsky"). There are about 3 ha of quartzite-like sandstones outcrops on the right bank of the Seim river (near the place where the Kleven River flows into it). Their age was previously determined as Eocene according to fauna findings. The main goal of current work was to determine the lithological and mineralogical features of eocenic sandstones. The investigated territory is confined to the north-eastern slope of the Dnipro-Donetsk depression in the area of influence of the Voronezh massif. Palaeogene sands underwent post-sedimentation changes. Lithological studies of sedimentary rocks prove that sandstones were formed in conditions of thermal catagenesis (at temperatures of 150-175oC). Separate parts of the rock (quartz cement, crustification zones) were formed due to partial dissolution of quartz grains in new geochemical and thermal conditions (at a temperature of about 200oC). Results of mineralogical and petrographical study of quartzite-like sandstones were given. Results show that native iron formation may be a consequence of a hydrothermal process, an electrochemical reaction, or can be formed under reduction conditions in a sedimentary basin.
Keywords: lithogenesis; thermal catagenesis; native iron; Eocene sandstone; sedimentary basin